The virtual child - Gilbertson, Richard J.; Behjati, Sam; Böttcher, Anna-Lisa; Bronner, Marianne E.; Burridge, Matthew; Clausing, Henrick; Clifford, Harry; Danaher, Tracey; Donovan, Laura K.; Drost, Jarno; Eggermont, Alexander M.M.; Emerson, Chris; et al. (Cancer discovery, 2024)
We are building the world's first Virtual Child-a computer model of normal and cancerous human development at the level of each individual cell. The Virtual Child will “develop cancer” that we will subject to unlimited virtual clinical trials that pinpoint, predict, and prioritize potential new treatments, bringing forward the day when no child dies of cancer, giving each one the opportunity to lead a full and healthy life.
Gesehen am 11.10.2024